American spaces : an overview of what's new - McCulloch, Janelle (Mulgrave, Vic. : Images ; [Woodbridge : ACC Distribution, distributor], 2007)
A vast array of possibilities for interior and landscape design is showcased in this new book, showing the best examples from North America. "American Spaces" is a direct response to the wealth of design activity across the mega-continent. In dynamic full-colour photography, this book provides a welcome look at the culturally diverse regions, and the latest trends in commercial spaces and atria, hospitality spaces and restaurants, leisure spaces and arts centres, public and special-purpose spaces. This book offers a plethora of ideas, and is a wealth of regional and international information.
Hospitality Restaurants -- Leisure & Arts Centers -- Public & Special Purpose -- Educational Facilities -- Commercial & Atria -- Index of Artists -- Acknowledgments.
Includes index.
Keywords: Public architecture -- United States -- Pictorial works; Interior architecture -- United States -- Pictorial works; Architectural design -- United States -- Pictorial works